2009
DOI: 10.1029/2008gl036397
|View full text |Cite
|
Sign up to set email alerts
|

Deep electrical resistivity structure of northwestern Costa Rica

Abstract: First long‐period magnetotelluric investigations were conducted in early 2008 in northwestern Costa Rica, along a profile that extends from the coast of the Pacific Ocean, traverses the volcanic arc and ends currently at the Nicaraguan border. The aim of this study is to gain insight into the electrical resistivity structure and thus fluid distribution at the continental margin where the Cocos plate subducts beneath the Caribbean plate. Preliminary two‐dimensional models map the only moderately resistive mafic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…This apparent lack of deep seismicity, together with the presence of the gap in Quaternary volcanism and an OIB-type geochemical signature for the volcanic rocks in the area (Hoernle et al, 2008), has led to several interpretations for the source of the adakites found in southeastern Costa Rica and western Panama (Fig. 5) (de Boer et al, 1991;Drummond et al, 1995). The hypothesis imply the melting of the slab edge by interaction with hot mantle through either a slab window (Johnston and Thorkelson, 1997;Abratis and Wörner, 2001) or a slab detachment (Gazel et al, 2011).…”
Section: Alternative Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…This apparent lack of deep seismicity, together with the presence of the gap in Quaternary volcanism and an OIB-type geochemical signature for the volcanic rocks in the area (Hoernle et al, 2008), has led to several interpretations for the source of the adakites found in southeastern Costa Rica and western Panama (Fig. 5) (de Boer et al, 1991;Drummond et al, 1995). The hypothesis imply the melting of the slab edge by interaction with hot mantle through either a slab window (Johnston and Thorkelson, 1997;Abratis and Wörner, 2001) or a slab detachment (Gazel et al, 2011).…”
Section: Alternative Modelmentioning
confidence: 99%
“…White arrows show direction and rate of plate motions relative to the Caribbean Plate (fixed) according to DeMets et al (1994DeMets et al ( , 2010 and DeMets (2001). Plate boundaries modified from Coffin et al (1998) and Lonsdale (2005). Black lines depict the coastline and international borders.…”
Section: O H Lücke and I G Arroyo: Costa Rican Subduction Zone 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…Strong constrains on fluid location is provided by electrical conductivity tomographic images (Baba, et al 2010;Brasse and Eydam 2008;Brasse, et al 2009;Ichiki, et al 2009). Over the last decade, the accuracy and The effect of hydration is to reduce sound velocities (green arrow).…”
Section: Magnetotelluricsmentioning
confidence: 99%